Effects of vascular endothelial growth factor-A and -C on wound healing in wild-type mice - Yukari Nakajima; Kanae Mukai; Kimi Asano; Toshio Nakatani (PLoS ONE, 2026)
This study aimed to investigate whether periwound subcutaneous administration of vascular endothelial growth factor-A (VEGF-A), VEGF-C, or both promotes wound healing in wild-type (WT) mice. A total of 40 9-week-old male BALB/c mice were used in this study. Two circular full-thickness skin wounds were created. Mice were treated with VEGF-A on day 4 after wound creation (VEGF-A group), VEGF-C on day 7 after wound creation (VEGF-C group), or VEGF-A and VEGF-C (VEGF-A + C group). The control group received subcutaneous saline injections on days 4 and 7. Photographs were taken, the wound area was measured, and the covering materials were changed for 15 days. Lymphography was performed before wound harvest. Tissues were harvested 4, 7, 10, and 14 days after wound creation and stained for lymphatic and blood vessels. The wounds in each group healed almost identically. No significant differences were observed between the VEGF-A, VEGF-C, and VEGF-A + C groups and the control group throughout the observation period. Similarly, no significant difference in the number of lymphatic and blood vessels within the granulation tissue after wound creation was observed between the VEGF-A, VEGF-C, and VEGF-A + C groups and the control group. Collecting lymphatic vessels did not regenerate across the wound, whereas capillary lymphatic vessels regenerated within the wound. Endogenous repair responses in acute wounds in WT mice progress relatively rapidly, and angiogenesis and lymphangiogenesis are sufficiently induced without VEGF-A or VEGF-C. Therefore, additional exogenous VEGF-A or VEGF-C may provide little incremental benefit, consistent with a ceiling effect.